Bartosz Adamczewski, Retelling the Law. Genesis, Exodus-Numbers, and Samuel-Kings as Sequential Hypertextual Reworkings of Deuteronomy. (European Studies in Theology, Philosophy and History of Religions 1; Frankfurt am Main: Peter Lang, 2012) - Lemański, Janusz (The Biblical Annals, 2015)
Book review: Bartosz Adamczewski, Retelling the Law. Genesis, Exodus-Numbers, and Samuel-Kings as Sequential Hypertextual Reworkings of Deuteronomy. (European Studies in Theology, Philosophy and History of Religions 1; Frankfurt am Main: Peter Lang, 2012). Pp. 376. US$ 82,95. € 58,70. ISBN 978-3-631-63034-1.